PENGARUH FOOD QUALITY DAN INOVASI PRODUK TERHADAP CUSTOMER SATISFACTION DI PENTOL NONA BENGKULU - Cahaya, Nilam; Ratnawili, Ratnawili (UM. Bengkulu, 2024)
The quality of a food product is very important for every founder of a food selling company. Apart from that, to increase consumer satisfaction, a business must innovate. The aim of this research is to determine the influence of food quality and product innovation on customer satisfaction at Pentol Nona Bengkulu. This type of research is a descriptive quantitative approach. The population in this research is all consumers at Pentol Nona Bengkulu within 1 month. Sampling in this study was determined using the unknown population formula so that the number of samples in this study was 96 respondents. The data collection techniques in this research are observation and questionnaires. The data analysis techniques used are multiple linear regression, coefficient of determination, and hypothesis testing. It was found that food quality has a positive effect on customer satisfaction of Pentol Nona Bengkulu City consumers, so the higher the food quality, the higher the customer satisfaction at Pentol Nona Bengkulu City. Product innovation has a positive effect on customer satisfaction of Pentol Nona Bengkulu City consumers, so the higher the product innovation, the higher the customer satisfaction at Pentol Nona Bengkulu City. Together, the food quality and product innovation variables influence the customer satisfaction variable at Pentol Nona, Bengkulu City. Keywords : Food Quality, Innovation Of Product, Customer Satisfaction